Effectiveness of a Tailored Behavioral Intervention to Improve Hypertension Control: Primary Outcomes of a Randomized Controlled Trial. Issue 2 (February 2015) - Friedberg, Jennifer P.; Rodriguez, Maria A.; Watsula, Michelle E.; Lin, Iris; Wylie-Rosett, Judith; Allegrante, John P.; Lipsitz, Stuart R.; Natarajan, Sundar
Abstract : Blood pressure (BP) control rates are suboptimal. We evaluated the effectiveness of 2 behavioral interventions to improve BP control via a 3-arm, randomized controlled trial of 533 adults with repeated uncontrolled BP, despite antihypertensive drug treatment for ≥6 months. The interventions were a tailored stage-matched intervention (SMI) or a nontailored health education intervention (HEI) of 6 monthly calls targeting diet, exercise, and medication. Control was usual care (UC). There were no baseline group differences. Baseline BP control was 42.6%, 40.6%, and 44.6% in SMI, HEI, and UC ( P =0.74), respectively; systolic BP (with SEs) was 136 (0.89), 137 (1.33), and 137 (0.96) mm Hg. Six-month control was 64.6% (SMI), 54.3% (HEI), and 45.8% (UC) ( P values for pairwise comparisons versus UC, 0.001 [SMI] and 0.108 [HEI]). At 6 months, systolic BP (SE) was 131.2 (1.05), 131.8 (0.99), and 134.7 (1.02) for SMI, HEI, and UC, respectively ( P values for pairwise comparisons versus UC, 0.009 for SMI and 0.047 for HEI). SMI led to lower systolic BP and better BP control than UC. SMI constitutes a new, potent approach to assist patients with uncontrolled hypertension to reach BP goals. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00286754.